Intermittent claudications of the hand after supracondylar humeral fracture in a 2-year old boy - Nora Knez; Karmen Jeričević; Luka Kelčec; Tomislav Vlahek; Dino Papeš (Liječnički vjesnik, 2023)
Supracondylar humeral fractures (SHF) are the most common fractures associated with concomitant neurovascular injuries in children. Pink pulseless hand (PPH) labels SHF presenting without a pulse in a wellperfused hand. Management of PPH after successful SHF reduction remains controversial. Some advocate „watchful waiting”, whereas others favor early exploration. We present a case of a 2-year-old boy with PPH and intermittent claudications 6 weeks after successful SHF reduction.